Lo cotidiano y lo social. la telenovela como texto y pretexto - Jesús Galindo (Estudios sobre las Culturas Contemporáneas)
The following proposals are suggested in this article: 1) to create a discursive model of analysis of the soap opera as a product of communication, dividing said model into four categories: a)narrative b)style c)language and d)argumentation, and 2) a general anthropological perspective of analysis, where ethnography is used to understand and explain the global phenomenon of soap operas as social and cultural events.